Factores determinantes de la longevidad: un recorrido por los estudios científicos. - Cando Tutalchá, Kevin Andrés (2024)
The study on the determinants of longevity addressed the complexity of this process by identifying individuals with longevity, defined as those who exceed the average life expectancy of their population of origin. With the aim of providing an accurate and up-to-date understanding of the factors that influence longevity, a comprehensive literature review was conducted focusing on the last five years, using reliable sources such as PubMed, Google Scholar, UpToDate, Scielo, Elsevier Scopus and ClinicalKey. The methodology used was a qualitative documentary approach, which included the collection and analysis of non-numerical data, such as texts and documents. This approach allowed each source to be critically examined to identify patterns, trends, and relationships among the determinants of longevity. The results revealed that longevity is influenced by genetic factors, lifestyle, diet, physical activity, physical and sociocultural environment, and sleep quality. In addition, detrimental factors such as resistance to stress and exposure to toxins were identified. The study highlights the importance of a comprehensive approach to promoting longevity, which considers both individual and contextual factors, providing a solid foundation for future research and strategies in health and well-being.